(untitled) (KULT_online, 2009)
This dissertation by chemist and German scholar Silke Jakobs uses natural scientists’ autobiographies to illuminate their relationship to the social sciences and art, placing particular emphasis on the historical development of the so-called "two culture" debate since the late 18th century, the differentiation or, rather, integration of the scientific disciplines, various education concepts, and natural scientists’ notions of nature and art. The autobiographies are interpreted with regard to social and scientific history, largely ignoring narrative construction. The primary finding is that natural scientists do, in fact, view both the social sciences and art as "other," but that their attitudes to these two (competing) fields differ markedly.